Penerapan Metode Monte Carlo Dalam Sistem Informasi Estimasi Pengerjaan Body Repair PT. Astra Daihatsu SM. Raja - Junita Rahmah; Ali Ikhwan; Muhammad Alda (Teknik Informatika Fakultas Ilmu Komputer, 2025)
PT Astra Daihatsu SM. Raja, a branch of PT. Astra International, Tbk operating in SM. Raja Medan, faces issues with the manual process of estimating time and cost for body repair services. This study aims to design and develop an estimation information system by applying the Monte Carlo method for the estimation calculations. The system is Android-based and can be accessed via smart devices. It is designed for employees to calculate estimates by inputting vehicle and repair data, after which the system automatically displays the estimated time and cost for repairs. By utilizing the waterfall development method and programming languages such as Java and PHP, this research successfully developed a system that provides more accurate and efficient repair estimates. The results of this study are expected to improve transparency and efficiency in the vehicle repair process at PT. Astra Daihatsu SM. Raja.